Generalisability of randomised trials of the programmed intermittent epidural bolus technique for maintenance of labour analgesia: a prospective single centre cohort study. (August 2019) - Gabriel, L.; Young, J.; Hoesli, I.; Girard, T.; Dell-Kuster, S.
Abstract: Background: Several randomised controlled trials show that maintenance of labour epidural analgesia with programmed intermittent epidural bolus reduces the maternal motor block compared with maintenance with a continuous infusion. However, these trials were usually restricted to healthy nulliparous parturients. To assess the generalisability of these randomised controlled trials to 'real-world' conditions, we compared maternal motor function (modified Bromage score) over time between healthy nulliparous and parous women using routinely collected quality-control data. Methods: After ethical approval, all parturients receiving programmed intermittent epidural bolus labour analgesia between June 2013 and October 2014 were included in this prospective cohort study. Bupivacaine 0.1% with fentanyl 2 μg ml −1 was used allowing for patient-controlled bolus every 20 min. The maternal motor function (primary outcome) was regularly assessed from insertion of the epidural catheter until delivery. Results: Of the 839 parturients included, 553 (66%) were nulliparous and 286 (34%) were parous. The parous women had a shorter median duration of epidural analgesia (3 h 59 min vs 5 h 45 min) and a higher incidence of spontaneous delivery (66% vs 37%). The probability of being in a certain Bromage category at birth was similar in nulliparous and parous women in a general additive model adjusting for duration of epidural analgesia, number of rescue top-ups, and number of catheter manipulations (cumulative odds ratio: 1.18; 95% confidence interval: 0.98–1.41). Parous women required a higher time-weighted number and volume of rescue top-ups. Conclusions: The results of the randomised controlled trials on a reduced motor block with programmed intermittent epidural bolus seem generalisable to parturients typically not included in these trials.